REFLECTIONS ON MULTIDISCIPLINARY WORK AND INTERGENERATIONAL RELATIONS, IN THE OLDER ADULTS PROGRAM OF THE COSTA RICAN TECHNOLOGY INSTITUTE, DURING 2012 - Castillo Rodríguez, Larissa (2015)
This article is based on a survey that aims at reflecting on two social policies: the multidisciplinary work and the intergenerational relations for the older people programs in universities, specifically at Costa Rican Technology Institute-TEC. On one side, the multidisciplinary work is a social policy present in the courses, the teaching-learning process, and the different projects connected to the TEC Program. On the other side, an aspect to be improved is the intergenerational relations in order to build a social support network for older people. The main goal of this survey is to visualize the TEC Program for older people by enhancing the multidisciplinary work and suggesting intergenerational projects as a way to fit this population into the academic context